Glycosmis pentaphylla (Rutaceae): A Natural Candidate for the Isolation of Potential Bioactive Arborine and Skimmianine Compounds for Controlling Multidrug-Resistant Staphylococcus aureus - Murugan, Natarajan; Srinivasan, Ramalingam; Murugan, Athiappan; Kim, Myunghee; Natarajan, Devarajan (Frontiers in Public Health, 2020)
Several multidrug-resistant organisms have emerged which increases the threat to public health around the world and a limited number therapeutics were available to counteract these issues. Thus, the researchers are trying to find out novel antimicrobials to overcome multidrug-resistant issues. The present study aimed to isolate antibacterial principles against the clinical isolates of multidrug-resistant Staphylococcus aureus from the ethyl acetate extract of Gycosmis pentaphylla. The isolation and structural characterization of bioactive compounds were carried out using various chromatographic techniques (TLC, column, HPLC, and LC-MS) and spectral studies such as FT-IR, CHNS analysis, 1H-NMR, and 13C-NMR. The antimicrobial potential of isolated compounds was assessed according to the standard methods. The isolated compounds were identified as arborine and skimmianine which exhibited the significant antibacterial effect with lowest MIC and MBC values against MDR S. aureus and in-vitro kinetic and protein leakage assays supported the antimicrobial activity. Significant morphological changes such as uneven cell surfaces and morphology, cell shrinkage and cell membrane damages were observed in the MDR S. aureus upon the treatment of arborine and skimmianine. The present investigation concludes that the isolated arborine and skinmmianine compounds from G. pentaphylla, harbor a strong antibacterial activity against MDR S. aureus and may be used as alternative natural drugs in the treatment of MDR S. aureus.